Identitas Pemuda Kelompok Seni Paijo - Mochammad Fiki Eko Syahputra Yudhoyono; Rizqi Ahmad Muzaki; Alvina Setiyawati; Dhiyaul Haqqi Al-Mumtaza (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This article discusses the Paijo art group as a medium for the formation and expression of the identity of today’s youth or Generation Z through the arts, especially in the field of theater. The shift from the New Order to the Reform Era has created an atmosphere that can lead youth to lose direction in their quest for identity. During the New Order era, "Gondrong" became a symbol of youth at that time, representing resistance and freedom of expression. However, the Reform Era, which has brought youth into the rapid development of technology and information, has created a gap between the millennial and Generation Z. Amidst this advancement, Generation Z is faced with global cultures that were previously difficult to access, resulting in many choices that ultimately lead youth into a crisis of identity. While in the New Order, binding policies produced a uniform and clear identity. The Paijo Art Group emerges as a reflective medium for youth in the process of discovering their identity through a creative and collaborative spirit. The symbols and emblems within the Paijo art group carry strong meanings that underlie the formation of this distinctive art group. This research is conducted to explore the importance of future goals for young people and to rise together, accompanied by the passionate fighting spirit they manifest within the Paijo art group, promoting the symbols and ideology of the group.